(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The new language situation in society quite naturally poses new challenges for the entire system of teaching the Russian language and studying it at school. The fact how important the correct, precise, expressive speech of a teacher is.